A Semantic Web Approach to Simplifying Trigger-Action Programming in the IoT - Corno, Fulvio; De Russis, Luigi; Roffarello, Alberto Monge (Computer (Long Beach, Calif.), 2017)
End-user programming environments for the IoT such as IFTTT rely on a multitude of low-level trigger-action rules that categorize devices and services by technology or brand. EUPont is a Semantic Web ontology that enables users to meet their needs with fewer, higher-level rules that can be adapted to different contextual situations and as-yet-unknown IoT devices and services.